2017
DOI: 10.15626/eco-tech.2010.059
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Impact of Iron and Aluminium Addition on the Anaerobic Digestion Process

Abstract: In this study, the impact of iron and aluminium salts addition on anaerobic digestion process was investigated. Mixture of primary and activated sludge collected at Vilnius wastewater treatment plant in Lithuania was digested under laboratory conditions by using anaerobic digester (W8, Amfield, UK). To compare the relative digestibility of iron-dosed (Fe-dosed) and aliuminium-iron-dosed (Al-Fe-dosed) sludge with un-dosed sludge three continuous experiments were made. Results showed that iron and aliuminium neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(11 reference statements)
1
1
0
Order By: Relevance
“…The current study showed a 19.65% and 35.16% reduction in the biogas volumes after CPR treatment with 100 mg/L of Al 3+ and Fe 3+ salts, respectively. This is in agreement with the range of 20%-50% reduction previously reported by Ofverstrom et al [30]. Although the previous studies were on mixed sludge, the current research provides data on SAS and compares the biogas reduction effects of alum and ferric salts.…”
Section: Effects Of Aluminium and Ferric Dosing On Biogas Productionsupporting
confidence: 92%
“…The current study showed a 19.65% and 35.16% reduction in the biogas volumes after CPR treatment with 100 mg/L of Al 3+ and Fe 3+ salts, respectively. This is in agreement with the range of 20%-50% reduction previously reported by Ofverstrom et al [30]. Although the previous studies were on mixed sludge, the current research provides data on SAS and compares the biogas reduction effects of alum and ferric salts.…”
Section: Effects Of Aluminium and Ferric Dosing On Biogas Productionsupporting
confidence: 92%
“…Lab-scale BT, AS dosed with Fe (Smith and Carliell-Marquet, 2009) 12-20% less biogas; 10-22% less methane Lab-scale AD, mixture of primary and activated sludge dosed with Fe (Ofverstrom et al, 2010) 20-50% less biogas…”
Section: Control Ammonia Toxicitymentioning
confidence: 99%